Failure Handling of Robotic Pick and Place Tasks With Multimodal Cues Under Partial Object Occlusion - Zhu, Fan; Wang, Liangliang; Wen, Yilin; Yang, Lei; Pan, Jia; Wang, Zheng; Wang, Wenping (Frontiers in Neurorobotics, 2021)
The success of a robotic pick and place task depends on the success of the entire procedure: from the grasp planning phase, to the grasp establishment phase, then the lifting and moving phase, and finally the releasing and placing phase. Being able to detect and recover from grasping failures throughout the entire process is therefore a critical requirement for both the robotic manipulator and the gripper, especially when considering the almost inevitable object occlusion by the gripper itself during the robotic pick and place task. With the rapid rising of soft grippers, which rely heavily on their under-actuated body and compliant, open-loop control, less information is available from the gripper for effective overall system control. Tackling on the effectiveness of robotic grasping, this work proposes a hybrid policy by combining visual cues and proprioception of our gripper for the effective failure detection and recovery in grasping, especially using a proprioceptive self-developed soft robotic gripper which is capable of contact sensing. We solved failure handling of robotic pick and place tasks and proposed 1) more accurate pose estimation of a known object by considering the edge-based cost besides the image-based cost; 2) robust object tracking techniques which work even when the object is partially occluded in the system and achieve mean overlap precision(OP)up to 80%; 3) contact and contact loss detection between the object and the gripper by analyzing internal pressure signals of our gripper; 4) robust failure handling with the combination of visual cues under partial occlusion and proprioceptive cues from our soft gripper to effectively detect and recover from different accidental grasping failures. The proposed system was experimentally validated with the proprioceptive soft robotic gripper mounted on a collaborative robotic manipulator, and a consumer-grade RGB camera, showing that combining visual cues and proprioception from our soft actuator robotic gripper was effective in improving the detection and recovery from the major grasping failures in different stages for the compliant and robust grasping.